Antike Mythologie in christlichen Kontexten der Spätantike - Leppin, Hartmut (2015)
It is well known that classical mythology outlasted the Christianization of the Roman Empire. This volume undertakes a new investigation of the complex conditions under which it continued to exist and thrive in Late Antiquity. Particular attention is devoted to the polemical and educational contexts in which classical mythology was often used, and to strategies designed to neutralize or assimilate it.